English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-01-11 15:35:20 · 6 answers · asked by styles4u 4 in Science & Mathematics Mathematics

6 answers

2^(-x) = 1/32
=> 2^(-x) = 1/(2^5)
=> 2^(-x) = 2^(-5)
=> -x = -5
=> x = 5.

2007-01-11 15:38:53 · answer #1 · answered by Scarlet Manuka 7 · 0 1

x =5

2007-01-11 16:30:50 · answer #2 · answered by RhondaJo 2 · 0 0

2^(-x) = 1/32
1/2^x = 1/32
2^x = 32 = 2^5
x = 5

2007-01-11 16:06:05 · answer #3 · answered by Northstar 7 · 0 0

2^-x = 1/32
ln(2^-x) = ln(1/32)
-xln(2) = ln(1/32)
-x = ln(1/32)/ln(2)
x = -ln(1/32)/ln(2)

2007-01-11 15:42:29 · answer #4 · answered by Anonymous · 0 0

2^-x = 1 / 32
2^(-x) = 1/(2^5)
2^(-x) = 2^(-5)
so
-x = -5
x = 5

Solved!!!

2007-01-11 15:40:58 · answer #5 · answered by fortman 3 · 0 0

2^(-x) = 1/32
ln(2^{-x}) = ln(1/32)
-xln(2) = ln(1/32)
x= - ln(1/32) / ln(2) = -ln( 2^{-5} )/ln(2) = - (-5) ln(2)/ln(2) = 5 .

2007-01-14 04:09:44 · answer #6 · answered by Anonymous · 0 0

fedest.com, questions and answers